Advances in paraganglioma–pheochromocytoma cell lines and xenografts. Issue 12 (December 2020) - Bayley, Jean-Pierre; Devilee, Peter
Abstract : This review describes human and rodent-derived cell lines and xenografts developed over the last five decades that are suitable or potentially suitable models for paraganglioma–pheochromocytoma research. We outline the strengths and weaknesses of various models and emphasize the recurring theme that, despite the major challenges involved, more effort is required in the search for valid human and animal cell models of paraganglioma–pheochromocytoma, particularly those relevant to cancers carrying a mutation in one of the succinate dehydrogenase genes. Despite many setbacks, the recent development of a potentially important new model, the RS0 cell line, gives reason for optimism regarding the future of models in the paraganglioma–pheochromocytoma field. We also note that classic approaches to cell line derivation such as SV40-mediated immortalization and newer approaches such as organoid culture or iPSCs have been insufficiently explored. As many existing cell lines have been poorly characterized, we provide recommendations for reporting of paraganglioma and pheochromocytoma cell lines, including the strong recommendation that cell lines are made widely available via the ATCC or a similar cell repository. Basic research in paraganglioma–pheochromocytoma is currently transitioning from the analysis of genetics to the analysis of disease mechanisms and the clinically exploitable vulnerabilities of tumors. A successful transition will require many more disease-relevant human and animal models to ensure continuing progress.